Craniofacial and Mandibular Morphometrics for Sex Determination in an Indian Population: A Radiographic Discriminant Function Analysis - Kiran K. Holikatti; Punnya V. Angadi; Chetan Belaldavar (Indian Journal of Forensic Medicine and Pathology, 2025)
Introduction: Sex determination based on skeletal features plays a crucial role in forensic identi𿿿cation. There is sparse data on the metric cranial and mandibular criteria for Indians. This study aimed to establish population-speci𿿿c standards for sex determination in the crania and mandibles of adults using logistic regression analysis. Materials and methods: The sample consisted of 300 participants (150 males, 150 females; age range: 18-30 yrs) of Indian origin. Fifteen standard cranial and 10 mandibular measurements were recorded on radiographic images and processed using a computer-aided drafting program (Adobe Photoshop 7 CS3 extended). To ascertain the usefulness of these parameters in sex prediction, a logistic regression analysis was performed. Results: All cranial parameters, except the upper facial height (G-ANS) and orbital measurements, showed sexual dimorphism. All mandibular parameters, except the mandibular angle, showed sexual dimorphism. The cranial measurements had a sex assessment accuracy of 86%, and the mandibular measurements had an accuracy of 82.7%. The combination of these parameters signi𿿿cantly improvedthe accuracy to 89.7%. Conclusion: This study on crania and mandibles of the Indian population clearly indicates that they have satisfactory potential for sex determination in adult Indians in forensic contexts. The width measurements, that is, bizygomatic breadth for the crania and bigonial breadth for the mandibles, were the most discriminatory.